SEX FOR SURVIVAL: THE FAILURE OF NEGOTIATION ON CONDOM USE BETWEEN FEMALE SEX-WORKERS AND THEIR MALE CUSTOMERS (A PHENOMENOLOGICAL STUDY) - Soedirham, Oedojo; Indarwati, Dian Ratna (Advances in Social Sciences Research Journal, 2020)
The problem of covert prostitution is challenging to solve because it cannot be controlled by the loccal health officers due to the difficulties in detecting the presence of female sex workers (FSWs) who do not claim their profession when the Social Service does the data collection. It causes the incidence of sexually transmitted infections (STIs) continues to increase, and it is difficult to prevent transmission of these diseases. The highest STI cases, based on data from the Ministry of Health of the Republic of Indonesia with a syndrome diagnosis approach and laboratory examinations according to risk groups for 2016-2018, suffered by FSWs as many as 93,798 cases. An increase in STI cases among FSWs shows that condom use among customers is still low. It is related to fewer negotiations with customers during sexual transactions. Prevention of STI transmission can be done by adhering customers to use condoms during sexual intercourse. This qualitative approach research was conducted to find out the ability of female sex workers to negotiate with customers about the use of condoms in every sexual transaction they do. The research approach was in the form of phenomenological studies and the informants were chosen based on their rich information on the issues through in-depth interviews. The informants in this research were FSWs, and their customers and shop owners were added as for research triangulation. The results showed that the ability of FSWs to negotiate with customers about the use of condoms is still low because FSWs are tempted to get money to live on. So sometimes they are tempted to get extra money from customers if the customers don't want to use condoms regardless of their own health. This study concludes that the economic needs of FSWs is still critical factors and also influences the ability to negotiate with customers about the use of condoms.